Observational evidence that urbanisation and neighbourhood deprivation are associated with escalation in chronic pharmacological pain treatment: a longitudinal population-based study in the Netherlands. Issue 4 (19th July 2012) - Leue, Carsten; Buijs, Servaas; Strik, Jacqueline; Lousberg, Richel; Smit, Jasper; van Kleef, Maarten; van Os, Jim
Abstract : Objective: To examine, in the light of the association between urban environment and poor mental health, whether urbanisation and neighbourhood deprivation are associated with analgesic escalation in chronic pharmacological pain treatment and whether escalation is associated with prescriptions of psychotropic medication. Design: Longitudinal analysis of a population-based routine dispensing database in the Netherlands. Setting: Representative sample of pharmacies, covering 73% of the Dutch nationwide medication consumption in the primary care and hospital outpatient settings. Participants: 449 410 patients aged 15–85 years were included, of whom 166 374 were in the Starter group and 283 036 in the Continuation group of chronic analgesic treatment. Main outcome measure: Escalation of analgesics (ie, change to a higher level of analgesic potency, classified across five levels) in association with urbanisation (five levels) and dichotomous neighbourhood deprivation was analysed over a 6-month observation period. Methods: Ordered logistic multivariate model evaluating analgesic treatment. Results: In both Starter and Continuation groups, escalation was positively associated with urbanisation in a dose–response fashion (Starter group: OR (urbanisation level 1 compared with level 5): 1.24, 95% CI 1.18 to 1.30; Continuation group: OR 1.18, 95% CI 1.14 to 1.23). An additional association was apparent with neighbourhood deprivation (Starter group: OR 1.07, 95% CI 1.02 to 1.11; Continuation group: OR 1.04, 95% CI 1.01 to 1.08). Use of somatic and particularly psychotropic co-medication was associated with escalation in both groups. Conclusions: Escalation of chronic analgesic treatment is associated with urban and deprived environments and occurs in a context of adding psychotropic medication prescriptions. These findings suggest that pain outcomes and mental health outcomes share factors that increase risk and remedy suffering.